Direito de permanecer: turismo de base comunitária e desenvolvimento endógeno na Ilha de Marajó - Pará - Brasil - BOULHOSA, Marinete da Silva (Universidade Federal do Pará, 2024)
This thesis analyzes community-based tourism on the island of Marajó, led by the coastal communities of Caju-una, Céu and Pesqueiro, in the municipality of Soure, which are part of the Soure Marine Extractive Reserve, in an attempt to understand how local communities are appropriating tourism. The objective is to understand how this way of developing tourism can contribute to the endogenous development and autonomy of these communities. To achieve this analysis and understanding, the following specific objectives are: identifying community tourism experiences on Marajó Island, as a collective social practice; analyze the forms of local organization for the development of community-based tourism, the agents and activities involved in the process; characterize the profiles of tourists/visitors and analyze the socialization processes of these tourist experiences and the connections with the tourist trade; and problematize public policies related to tourism on the Island. The analysis of communitybased tourism practices was based on the principles of endogenous development, which values local resources and the participation of communities in the development process, and post-development, which questions traditional notions of development, bringing centrality and resistance of the place. The research also considered the perspectives of decoloniality, buen vivir and ecosocioeconomy, which propose a non-Eurocentric and more holistic view of development, considering power relations and the worldviews of local communities. The research is of an applied nature, with a qualitative and quantitative approach, with exploratory, descriptive and explanatory objectives, and bibliographical research procedures, field research and action research. The research results pointed to the emergence of an embryonic process of tourism in Marajó that takes place based on local initiatives, which despite the problems and limitations it presents, have generated socioeconomic benefits for communities, in contrast to the exclusionary conventional tourism model that has been occurring for decades in Marajó. The results of the thesis will contribute to the understanding of communitybased tourism practices on the island of Marajó and to reflection on fairer and more democratic development alternatives, considering local specificities and the communities perspectives.